PERBEDAAN KADAR FORMALIN PADA TAHU PUTIH DI TINGKAT PRODUSEN DAN PEDAGANG KOTA SEMARANG TAHUN 2016 - Misrina Ulil Aziza; M. Zen Rahfiludin; Dina Rahayuning Pangestuti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Indonesian population more to consume plant-based protein than animal-based protein. Plant-based proteins that consumed by many people are tofu and tempeh. Nowadays, in the market is circulating tofu which added harmful preservatives such as formalin. The addition of formalin in tofu can be done by producer or trader. This study aimed to analyze the differences of formaldehyde levels in tofu at the level of producers and of traders in Semarang. This study is quantitative, which use observational analytic type by a cross-sectional plan. The total sample is 24 tofu samples consist of 5 tofu at producer level and 19 tofu at traders level. Analysis of correlation between knowledge, attitude of traders with the presence of formalin using Fisher's exact test. Analysis of tofu sample done qualitatively using chromatropic acid, if positive followed by quantitative analysis using spectrophotometric method. Laboratory test results stating that all the tofu samples at producer level do not contain formaldehyde and 26% of tofu samples at traders level positive containing formalin. Levels of formaldehyde in the samples varied between1.55 to 5049,91 ppm. Tofu with positive formaldehyde content contained in traders with less knowledge category (p-value = 0.011). There is no relationship between attitude of traders with presence of formaldehyde in tofu (p-value = 1.000). There is no relationship between knowledge with attitudes of traders towards the use of formalin in tofu (p-value = 1.000). Education about dangers of formaldehyde should be done intensively and thoroughly to businesses. Society should improve skills in choosing safe food.